Truth, reparations and social cohesion transitional justice lessons from Peru - Bunselmeyer, Elisabeth (Abingdon, Oxon : Routledge, 2020)
This book addresses the effectiveness of transitional justice mechanisms for repairing social cohesion. Truth commissions and reparation programs are implemented worldwide to enhance social cohesion, peace and democracy in post-conflict settings. Most claims about transitional justice measures are, however, normatively and not empirically based.The book questions whether attention from a truth and reconciliation commission can truly change the lives of the violence-affected people and whether monetary compensations or communal projects in form of milk cows can ever truly "repair" the harm suffered. The within-country comparative case study analyzes the effects of the commission and reparation program in Peru. It studies the post-conflict situation and the development of social cohesion in communities affected by the internal armed conflict. Using detailed empirical data this analysis reveals why the "reparation" of social cohesion in Peru was an impossible task. Contributing to a broader understanding of the impact of nationally applied transitional justice instruments in local settings, the book further offers a new framework for analyzing social cohesion as one of the aims of transitional justice processes. Offering a detailed account of transitional justice processes and social cohesion on the micro level, as well as an important analysis of their relationship, this innovative monograph will be invaluable for transitional justice scholars and students, as well as for international political and societal actors who are involved in transitional justice measures.
OCLC-licensed vendor bibliographic record.
Keywords: Transitional justice -- Peru; Human rights -- Peru; LAW / General; LAW / Comparative; LAW / Criminal Law / General